MEDICAL SERVICE IN LANSOT PUBLIC MEDICAL CENTER, TOMOHON CITY - PANGEMANAN, GRANDY; ROMPAS, WELSON; RURU, JOORIE (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study was to find out how the health services available at the health center Lansot, Tomohon City.One form of government efforts in providing health to the community, in each district government agencies are built aspublic health service delivery units, namely community health centers or also called puskesmas. Puskesmas is afunctional organization that organizes health efforts that are comprehensive, integrated, equitable, acceptable andaffordable to the community, with active community participation and using the results of the development of appropriatescience and technology, at a cost that can be borne by the government and the community. The health effort is carriedout by focusing on services for the wider community in order to achieve optimal health status, without ignoring thequality of services to individuals. In accordance with the vision of the local health center that is 'Becoming a quality,independent and affordable basic health service center for the whole community'. Lansohon City Health Center Tomohonalways strives to serve well in all care needs including curative, preventive, promotive and rehabilitation services in thehope that patients who receive health services feel satisfied. Public. Service dissatisfaction can come from the cleanlinessof the waiting room, the cleanliness of the treatment room, and the negligence of the officers in handling patients. Thisstudy uses a theory according to Moenir by using several factors namely employee awareness, the existence of rules,organizational factors, ability and skills factors, service facility factors. From here we can see the awareness ofemployees about the actions given to the tasks that are still not good for example in taking a queue number and even theexisting rules must be implemented in the organization, the existence of these rules has been applied in health centersand every employee who does not run the existing rules will be given sanctions according to the level of violation thathas been made and more disciplined for employees during working hours. It is expected that from this research can makeemployee awareness increase even though all applicable rules can actually be applied in accordance with applicableprocedures.Keywords: Services, Health, Public health center